If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 7q = 15 + 6q Solving 10 + 7q = 15 + 6q Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-6q' to each side of the equation. 10 + 7q + -6q = 15 + 6q + -6q Combine like terms: 7q + -6q = 1q 10 + 1q = 15 + 6q + -6q Combine like terms: 6q + -6q = 0 10 + 1q = 15 + 0 10 + 1q = 15 Add '-10' to each side of the equation. 10 + -10 + 1q = 15 + -10 Combine like terms: 10 + -10 = 0 0 + 1q = 15 + -10 1q = 15 + -10 Combine like terms: 15 + -10 = 5 1q = 5 Divide each side by '1'. q = 5 Simplifying q = 5
| 2.6-8n=5n+19 | | 9+7x=6x+20 | | 8x-44=52 | | -0.2(x-6)=6 | | 11m^5= | | 4(d+2x)-5=3(3x+7) | | 7x-15=5x+7 | | 2c-5=c+9 | | x+x+81=x+144 | | -6+3w=-21 | | -6t-12-6t=10(t+5)+4 | | 2[1-3(w+2)+2(w+3)]=5w | | x-5-(-2)+2x=7 | | Q-2.4=1.8 | | 3b=6v+3b | | 10y+18=-3(5y-7)+5y | | 4n^2-4n-6=0 | | K-56=107 | | y+5=-7x-21 | | x^2-y^2-3x+3= | | x+x+2+x+2=75 | | (x^2-2x-1)+(2a^2+2a+3)= | | 3g+2(-5+2g)=1-g | | 2(a+1)+4a=-10 | | x^2(x^2+x+1)=0 | | 8(p+1)-6p=24 | | 5(x+4)=3x+14 | | 625=(x^2)+(x^2)+6x+9 | | 9k-32=6k+8 | | x/7=5 | | 12x+7y=-35 | | x^3+125y^3= |